1999
DOI: 10.1093/treephys/19.1.53
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aqueous transport of CO2 in xylem sap on gas exchange in woody plants

Abstract: The influence of CO(2) transported in the transpiration stream on measurements of leaf photosynthesis and stem respiration was investigated. Measurements were made on trees in a temperate forest in Scotland and in a tropical rain forest in Cameroon, and on shrubs in the Sahelian zone in Niger. A chamber was designed to measure the CO(2) partial pressure in the gas phase within the woody stems of trees. High CO(2) partial pressures were found, ranging from 3000 to 9200 Pa. Henry's Law was used to estimate the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
137
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 18 publications
4
137
0
1
Order By: Relevance
“…(4) Sapflow could transport part of the CO 2 respired by the stem [12,23,30,33] and it could release it in the upper parts of the stem. However, Edwards and Wullschleger [11] and Ceschia [7] found little evidence of the effect of the sapflow on stem respiration.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Sapflow could transport part of the CO 2 respired by the stem [12,23,30,33] and it could release it in the upper parts of the stem. However, Edwards and Wullschleger [11] and Ceschia [7] found little evidence of the effect of the sapflow on stem respiration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most studies of plant metabolic scaling have been based on the aboveground parts and have ignored respiration of the roots, which is very difficult to measure (23). Furthermore, the flow of dissolved CO 2 in the sap brings into question the accuracy of estimating whole-tree respiration based on measuring small portions of large trees using the standard clamp-on chambers that are commercially available (16,(27)(28)(29)(30).Given the methodological difficulties inherent in whole-plant physiological studies, it is not surprising that there have thus far been no empirical measurements of complete whole-plant respiration, including roots, that have a reasonable sample size and encompass a wide range of plant sizes (2,22,26,(31)(32)(33)(34). Accurate and efficient methods using whole-plant chambers to measure respiration rates have recently been developed (5,18,19,(24)(25)(26) and can be applied to assess metabolic scaling (Fig.…”
mentioning
confidence: 99%
“…Furthermore, most studies of plant metabolic scaling have been based on the aboveground parts and have ignored respiration of the roots, which is very difficult to measure (23). Furthermore, the flow of dissolved CO 2 in the sap brings into question the accuracy of estimating whole-tree respiration based on measuring small portions of large trees using the standard clamp-on chambers that are commercially available (16,(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…These values are corresponding well with results from other studies from various trees. Levy et al (1999) reported efflux rates between 6.0 (day time) and 3.5 (night time) μmol m -2 s -1 in a Combretum micranthum G. Don shrub in Cameroon, whereas maximum values of 9.9 μmol m -2 s -1 are also known for Schima superba Gardner & Champ. trees in the subtropics of southern China (Zhu et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…One study using continuous measurements with open dynamic chambers was conducted in a Schima superba Gardner & Champ. plantation, in the subtropics of southern China (Zhu et al 2011), and another in a subtropical Combretum micranthum G. Don shrub growing in Cameroon (Levy et al 1999). These studies generally found a positive relation between xylem sap fl ux and CO 2 effl ux, but the fi ndings regarding the overall effect of the water transport were quite controversial compared to the results with trees from temperate and boreal forests.…”
Section: Introductionmentioning
confidence: 98%